2024
DOI: 10.1111/iwj.14874
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride glucose index as a sensitive predictor for the risk of MACCEs in patients with diabetic foot ulcers: An ambispective longitudinal cohort study

Rongyan Wei,
Shangyu Chen,
Xiuxian Huang
et al.

Abstract: The triglyceride glucose (TyG) index has been confirmed a predictive value for type 2 diabetes mellitus (T2DM). However, no research has yet confirmed whether there is a linear correlation between the TyG index and MACCEs in DFUs. The present study aimed to delve into the association between the TyG index and the risk of MACCEs in patients with DFUs. A total of 960 inpatients with DFUs were recruited. All participants were followed up every 6 months for 11 years with a median of 83 months. According to the cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…According to a variety of research, individuals with DM may benefit from using the triglyceride-glucose index (TyG), a surrogate marker of insulin resistance [ 12 , 13 ], and urine albumin-creatinine ratio (UACR), employed to detect microalbuminuria and nephropathy in a patient with DM [ 14 , 15 ] as risk factors for CVD in patients with DM. Recent machine-learning research has identified phosphate, blood urea nitrogen, troponin, and specific electrolytes as predictive factors for CVD in individuals with diabetes mellitus (DM) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a variety of research, individuals with DM may benefit from using the triglyceride-glucose index (TyG), a surrogate marker of insulin resistance [ 12 , 13 ], and urine albumin-creatinine ratio (UACR), employed to detect microalbuminuria and nephropathy in a patient with DM [ 14 , 15 ] as risk factors for CVD in patients with DM. Recent machine-learning research has identified phosphate, blood urea nitrogen, troponin, and specific electrolytes as predictive factors for CVD in individuals with diabetes mellitus (DM) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%